Wladimiro de Acosta, arq. (1910-1967) - Presbisch, Alberto; Méndez Mosquera, Carlos A.; Borthagaray, Juan Manuel; Solsona, Justo; Flank, Jorge
Homenaje al arquitecto.
Keywords: ACOSTA, WLADIMIRO; TRAYECTORIA PROFESIONAL